Impact of commercial bank credit on agricultural output in Nigeria - Oyelade, Aduralere O. (Array, 2019)
Purpose. The purpose of this study was to investigated the impact of commercial bank credits on agricultural output in Nigeria over the period 1980 to 2015 by setting three specific objectives which are to examine the trend of commercial bank credit and agricultural output in Nigeria; to investigate the effect of commercial bank credit on agricultural output in Nigeria and to investigate the effect of commercial bank credit on subsector of agriculture in Nigeria. The trend analysis and the impact of commercial bank credit on subsector of agriculture in Nigeria make this work unique and different from other studies in this area. Trend analysis was used to achieve the first objective and fully modified ordinary least square (OLS) for objective two and three. Methodology. The study employed Fully Modified Ordinary Least Squares (FMOLS) approach. Findings. It was evidenced that interest rate on commercial banks’ credit to agriculture and deposit money bank’s assets are statistically significant in determine agricultural output in Nigeria within the period considered. Also, commercial bank loan on agriculture and deposit money bank’s assets determine the output of crop production in Nigeria; commercial bank loan on agriculture and interest rate on commercial banks’ credit to agriculture determine the output of livestock production in Nigeria and commercial bank loan on agriculture and interest rate on commercial banks’ credit to agriculture determine the output of forestry in Nigeria while commercial bank loan on agriculture and interest rate on commercial banks’ credit to agriculture determine the output of fishing in Nigeria. Limitations. This study is limited because the study does not include other variables that determine the output of agricultural sector in Nigeria. Also, other theories and methods can still be used by other researcher to make it different from this work.